A possible mechanism for the formation of an eastward moving auroral spiral - Maetschke, Katharina N.; Kronberg, Elena A.; Partamies, Noora; Grigorenko, Elena E. (Frontiers in Astronomy and Space Sciences, 2023)
The generation process of auroral spirals is described by different theories varying for their morphology and surrounding conditions. Here, a possible mechanism is proposed for an eastward moving auroral spiral, which was observed in Tromsø, Norway, during the expansion phase of a substorm on 18 September 2013. Measurements from the THEMIS-A and Cluster spacecraft were analyzed, which were located up to ∼10 R E duskward from the spiral generator region in the magnetosphere. Precursory to the spiral observation, concurrent magnetic field dipolarizations, flow bursts and electron injections were measured by the Cluster satellites between 13.6 and 14.2 R E radial distance from Earth. A local Kelvin-Helmholtz-like vortex street in the magnetic field was detected at the same time, which was likely caused by bursty bulk flows. The vortex street was oriented approximately in the X-Y (GSE) plane and presumably propagated towards the source region of the spiral due to a high dawnward velocity component in the flow bursts.The observations suggest that the spiral can have been generated by an associated vortex in the magnetotail and then mapped along the magnetic field lines to the ionosphere. To better understand the role of the ionosphere in auroral spiral generation, in future more mesoscale observations are required.